Օտարման դրաման Որբունու «Փորձը» և Շահնուրի «Նահանջը առանց երգի» վեպերում - Սարիբեկյան, Հրաչյա (Արմավ հրատ.)
The article explores the issue of individual alienation in the novels of Franco- Armenian writers Zareh Vorpuni“ The Attempt” ( 1929) and Shahan Shahnur “ Retreat without Song”( 1929). В статье исследуется проблема отчуждения личности в романах французско- армянских писателей Заре Ворбуни «Попытка» (1929) и Шахана Шахнура «Отступление безпесни » ( 1929).
Keywords: Գրականագիտություն